PHYSICAL STABILITY TEST HAIR TONIC COMBINATION Cinnamon (Cinnamomum burmanii) ESSENTIAL OIL AND VCO (VIRGIN COCONUT OIL) WITH CYCLING TEST METHOD AND IRRITATION TEST ON THE RABBIT - Junvidya Heroweti; Danang Novianto Wibowo; Arini Najikhatal Ulya; Desmita Linda (Jurnal Farmasi Sains dan Praktis, 2023)
Cinnamon (Cinnamomum burmanii) and VCO (Virgin Coconut Oil) essential oils contain cinnamaldehyde and lauric acid which have potential for hair growth, they can affect the physical stability of hair tonic preparations. This study aims to determine the physical stability and determine the effect of the irritation effect on hair tonic preparations of a combination of cinnamon essential oil and VCO. Cinnamon essential oil hair tonic preparations were made with a concentration of 1% (F1), 3% (F2), and 5% (F3) and then tested for physical characteristics including organoleptic tests, homogeneity, pH, density test, and viscosity. Evaluation of physical stability was carried out using the cycling test method. Data were statistically analyzed using One Way Anova. The results of the irritation test were analyzed descriptively using the primary irritation index obtained from the appearance of erythema and edema on the rabbit's skin. Observation of the physical stability test on organoleptic and homogeneity showed that formula I had a cloudy white color, a characteristic cinnamon aroma, a slightly thick liquid, and was homogeneous; formula 2 and 3 has a clear color, characteristic of cinnamon aroma, slightly viscous and homogeneous liquid; stable pH in formula 2; stable density in formulas 1, 2 and 3; and stable viscosity in formulas 2 and 3. The results of the hair tonic irritation test showed that the primary irritation index for F1, F2, and F3 was 0.0; 0.3; 0.3 and it can be concluded that F2 and F3 can irritate with very mild categories.